Core–Shell Carbon Nanofibers‐NiFe Structure on 3D Porous Carbon Foam: Facilitating a Promising Trajectory toward Decarbonizing Energy Production. (7th November 2022) - Pham, Tung Ngoc; Samikannu, Ajaikumar; Vincze, Zsuzsanna; Zettinig, Peter; Tesfalidet, Solomon; Wågberg, Thomas; Mikkola, Jyri‐Pekka
Abstract: In this work, a low‐cost, light‐weight, highly efficient, and durable electrode in which NiFe‐layered double hydroxide is electrodeposited on a carbon nanofiber (CNF) core supported on a carbon foam (CF) is introduced. The resulting 3D NiFe‐CNFs‐CF electrode shows excellent oxygen evolution reaction and hydrogen evolution reaction performance in alkaline media. When used as an anode and a cathode in the same cell, a current density of 10 mA cm −2 is achieved, at a cell voltage of 1.65 V. Moreover, good stability over a long testing time (50 h) is demonstrated. The ternary hybrid electrode gives rise to an excellent performance‐to‐weight ratio owing to its very low bulk density (≈34 mg cm −3 ) inherited from super lightweight components composed of CF and CNFs. The developed electrode can potentially be used in large‐scale alkaline water electrolysis, in facilities such as offshore hydrogen production platforms, which can complement the variable renewable energy production of wind farms through hydrogen storage and fuel cells. Abstract : In this study, NiFe‐layered double hydroxide decorated on carbon nanofibers‐carbon foam electrode with a 3D porous core–shell structure is introduced. The extremely low bulk‐density electrode possesses an extremely high performance‐to‐weight ratio, high electrocatalytic activity, and excellent durability for the overall water‐splitting reaction.